Pneumoparotid: A Review - Aljeaid, Dhaifallah; Alotaibi , Ohoud (New Horizons in Medicine and Medical Research Vol. 10, 2022)
Pneumoparotid is an uncommon cause of enlargement of the parotid gland. It is due to reflux of air through Stensen’s duct into the parenchyma of the parotid gland. This review discusses the definition, epidemiology, clinical presentation, pathophysiology, diagnosis and management of pneumoparotid. The aim of this review is to increase the awareness of the health care professionals and the public about an interesting, rare but well-documented clinical entity.